2006
DOI: 10.1016/j.jmwh.2006.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disorder, affecting between 4% and 8% of reproductive aged women. This syndrome, a complex disorder with multiple components, including reproductive, metabolic, and cardiovascular manifestations, has long-term health concerns that cross the life span. The diagnostic criteria for PCOS are ovarian dysfunction evidenced by oligomenorrhea or amenorrhea and clinical evidence of androgen excess (e.g., hirsutism and acne) in the absence of other conditions that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 22 publications
(76 reference statements)
2
25
0
1
Order By: Relevance
“…The reason of this effect is still not known. In our study, FSH levels were lower and LH levels were higher in the patient group than the control cases and these findings were consistent with the previous studies [11,27,28]. In our study, we identified that FSH and nesfatin-1 had a positive correlation in the patient group, but the reason of this statistically significant correlation can be due to numerical decrement of both parameters in the same group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The reason of this effect is still not known. In our study, FSH levels were lower and LH levels were higher in the patient group than the control cases and these findings were consistent with the previous studies [11,27,28]. In our study, we identified that FSH and nesfatin-1 had a positive correlation in the patient group, but the reason of this statistically significant correlation can be due to numerical decrement of both parameters in the same group.…”
Section: Discussionsupporting
confidence: 93%
“…In 50-80% of women, insulin resistance (IR) were reported and it was found that there was a direct correlation between insulin levels and severity of PCOS [9,10]. Additionally, the possibility of having metabolic syndrome is more than four times higher in women with PCOS than in non-PCOS women [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…alterations in the secretion of gonadotropin-releasing hormone, defect in androgen synthesis and development of insulin resistance. 16 One of the numerous theories proposed to explain pathogenesis of the syndrome is the disturbance of the hypothalamic-pituitary axis, resulting in disarranged gonadotropin secretion by the hypothalamus with a consequent elevation of luteinizing hormone (LH) levels and normal and/or low follicle-stimulating hormone (FSH) levels. 14 A number of studies have also indicated that insulin resistance is the key pathophysiological element for development of the syndrome.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…So, ovulation does not occur and the ovaries produce more immature eggs. These eggs turn into cysts and the ovaries become large and studded with numerous cysts (11) . Nowadays the PCOS are interlinked with many disorders and it is not easy to diagnose the symptoms only with the help of ultrasonography but with some active measures like serum analysis for the detection of the hormonal levels.…”
Section: Introductionmentioning
confidence: 99%